Fördomsfullhet och tolerans i samlevnadsundervisningen - Bäckman, Maria (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1998)
If the aim of the first sex education in Sweden was to implant a certain behaviour and a certain moral in the youth, then one of the main aims today can be said to be to shatter prejudice. This article discusses the topic of homosexuality in sex education. Sex education is often seen as a desirable meeting between an enlightened and broad-minded ideal of equality and a collection of prejudiced positions. The method the studied teacher uses is to bring up widespread notions in order to then discuss and puncture them. One could say the aim of the educations is to reduce the distance between heterosexuals and homosexuals in order to increase tolerance. However, it is not quite as simple as going from being prejudiced to becoming tolerant — young people are often both at the same time. The adolescents seldom set a heterosexual norm or normality against a homosexual deviation when they discuss homosexuality in the classroom or in the interviews, but rather their understanding of homosexuality and homosexuals is much more structured by reflections on biological sex. The images of the homosexual man and the homosexual woman are constructed with the help of notions about differences and similarities between male and female. The sexual categories also contribute to homosexuality not being interpreted as a shared phenomenon. Instead a very clear division is made between male and female homosexuality. In the same way that antipathies are evoked and strengthened according to how the homosexual individual is either sexualized or de-sexualized, the significance the young people place in the sex of the individual is shown in that the gay male is almost always more negatively regarded than the lesbian woman. The male cross-over provokes more than the female one at the same time as the sexual activity is reserved for the gay male and does not seem to apply to the lesbian.